2019
DOI: 10.1177/0300060519845974
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter research on tumor and pregnancy outcomes in patients with early-stage cervical cancer after fertility-sparing surgery

Abstract: Objective To investigate tumor and pregnancy outcomes after fertility-sparing surgery for cervical cancer. Methods A total of 83 patients with cervical cancer who received fertility-sparing surgery at 10 gynecologic cancer research centers in Henan Province were enrolled from January 2010 to June 2016. Clinical data and follow-up results were collected. Of them, 78 had cervical squamous carcinoma and five had cervical adenocarcinoma. International Federation of Gynecology and Obstetrics (2009) staging showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 16 publications
(25 reference statements)
0
32
0
Order By: Relevance
“…In light of our results, professionals conducting CIN follow-ups should take into account women's specific concerns about fertility and pregnancy planning. As shown in cancer and fertility research [51, 52], the possibility of fertility-sparing approaches to preserve the reproductive potential of women affected by cervical cancer should be discussed with patients.…”
Section: Discussionmentioning
confidence: 99%
“…In light of our results, professionals conducting CIN follow-ups should take into account women's specific concerns about fertility and pregnancy planning. As shown in cancer and fertility research [51, 52], the possibility of fertility-sparing approaches to preserve the reproductive potential of women affected by cervical cancer should be discussed with patients.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that radical/ subradical trachelectomy is a safe and effective fertilitysparing approach for young women with early cervical cancer. 23 Post-surgery pregnancy rates could be as high as 78.26% (54/69) and all patients had good pregnancy outcomes. In this study, approximately 13.25% (11/83) of patients received subradical trachelectomy.…”
Section: Discussionmentioning
confidence: 87%
“…A total of 68 studies were included in this study. Tables 2 , 3 , 4 , 5 , 6 show the data on 3592 patients based on surgical treatment ( 37 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 110 , 111 , 112 ).…”
Section: Resultsmentioning
confidence: 99%